Light speed: catch me if you can - Mahdi, Mohd Adzir (Universiti Putra Malaysia Press, 2010)

(untitled)
Optical communications have been vigorously touted as the future of communications due to its many benefits such as amazing speed, enormous capacity and low transmission loss. The emergence of the optical wavelength-division multiplexing (WDM) scheme has further strengthened its position as the premier communication method to date. Nevertheless, optical communication is still hindered by a number of weaknesses, in particular the accumulated loss in long distance transmission and the need for multi-wavelength laser sources for WDM systems. The advent of various types of optical amplifiers strives to counter transmission attenuation in optical fiber. The two main players in the field are the erbium-doped fiber amplifiers and the Raman amplifiers, with their own individual advantages and weaknesses. Resourceful researchers have been able to combine both types to create hybrid amplifiers that enjoy the best features of both while downplaying their drawbacks. Additionally, the introduction of the remote pumping scheme has eliminated geographical and infrastructural obstacles which were strongly associated with optical amplifiers in the past.The Optical WDM system necessitates the employment of a multi-wavelength laser source that can provide multiple channels at high output. Multi-wavelength fiber lasers have been able to fill this need very well by generating lasers with low noise and smaller channel spacing, which allows more channel per transmission. These fiber lasers have taken advantage of the scattering effect in optical fiber, mainly the Brillouin scattering which enables the generation of multiple laser channels with small spacing of 0.089 nm. The integration of fiber lasers with erbium and modifications of the structure have allowed for a higher number of channels with wider tuning range. Such improvements have elevated the status of fiber lasers as an efficient and cost effective choice for deployment in optical WDM communications.Optical communication has already displayed great ability at this early stage and promises even more. This lecture serves to portray the current state of the technology and the significant contributions that have led to its current prominence and promise of an outstanding future